Human Resources and Livestock Sustainability: Exploring the Role of Workforce Training in Reducing Environmental Impact - Ainul Kholipah, Siti (Livestock Science & Innovation Journal, 2024)
The livestock sector is a major contributor to greenhouse gas (GHG) emissions and environmental degradation, necessitating sustainable practices. This study examines the role of workforce training in promoting sustainability, focusing on GHG reduction, resource efficiency, and sustainable management. Using a quantitative approach, data was collected from 500 livestock workers across 50 farms in Brazil, India, and South Africa. Stratified random sampling ensured diversity in training exposure. A structured questionnaire captured workers' perceptions, while GHG emissions, water use, and land utilization were sourced from farm records. Results show that structured training programs led to a 20% reduction in GHG emissions, a 15% improvement in water efficiency, and a 12% reduction in land degradation. Workers trained with digital tools retained 30% more sustainable practices and adopted waste management techniques 25% more effectively. Peer learning increased participation by 40%, fostering long-term adherence to eco-friendly methods. The impact is clear: farms implementing structured training reduce operational costs, comply better with environmental regulations, and enhance sustainability. Policymakers should develop scalable training programs, integrating digital tools and culturally relevant learning to maximize adoption. Incentives supporting sustainability training could drive industry-wide improvements in livestock production. This study highlights workforce training as a key strategy for reducing environmental impact in livestock farming. Equipping workers with sustainable skills enables tangible environmental benefits while improving farm efficiency and economic viability.